The Influence of Fast Method Health Education on Nurses' Knowledge in Early Detection of Stroke Disease at Labuang Baji Regional Hospital, Makassar City - Noviar, Rizki Andita; Belangi, Siska Putri; Suminar, Saka; Sallo, Andi Kamal M.; Listina, Osie; Fahamsya, Arifina (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Stroke is a medical emergency because it is time-related and requires fast, precise and careful treatment. Optimal management can prevent death and permanent disability. One strategy to increase awareness of stroke attacks can be done through education in the form of audiovisual methods which contain information about early detection of stroke. The aim of this research is to find out the influence of FAST method education on nurses' knowledge in early detection of stroke. This research is quantitative research using pre-experimental design. The type of test used is the Wilcoxon test with the research results being the pre test. The conclusion of this research is. There is an influence of FAST method counseling on nurses' knowledge in early detection of stroke with a value of P = 0.000. The results of this research can add information and input for health workers to improve the quality of health services in preventing strokes.